SPECIFIC ASSESSMENT OF THE QUALITY OF MATHEMATICS KNOWLEDGE LEVEL OF ECONOMISTS IN COMPETENCE PARADIGM - Rif V. Sagitov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The issue of mathematics education of economists has become more acute due to new educational paradigm accepted in standards of the third generation. The competence approach envisages subject support of professional competences of graduates of higher economics school. Mathematics in economics specializations acts as a cultural competence and cannot affect professional competences of economists. The article provides pedagogical technology for assessing the quality of mathematics training of economists by checking their skills of making mathematic calculations which can be necessary in their professional work. Along with substantiation of the given technology the author shows how to compile tests in this format.